The determinants of foreign direct investment inflows in Malaysia / Amirul Hakim Mohd Johari - Mohd Johari, Amirul Hakim (Faculty of Business and Management, 2017)
This study examines the relationships that between foreign direct investment (FDI) and the determinants economic growth (GDP), exchange rate (ER) and inflation rate (IR) from the year of Q1 2010 to Q3 2017 which contains quarterly data. This data was analyzed by using Autoregressive Distributed Lag method in order to define the statistical relationship among the variables. Besides, this study was used Autoregressive Distributed Lag methods and proceed with Descriptive Analysis, Diagnostic Checking, long run and short run form and Unit Root tests. In Diagnostic Checking, some tests done to check the significant presents of autocorrelation, heteroscedasticity, the normality of data distribution and model specification. The result of this study shows that there is a significant relationship between the foreign direct investment (FDI) and the economic growth (GDP) and exchange rate (ER) while inflation rate (IR) did not have any relationship with the Foreign Direct Investment. As conclusion, for the studies shows that the GDP, ER and IR become the factors that affecting the FDI decision in Malaysia.